Analisis Job Mismatch pada Pelatihan Vokasi Nonformal: Hasil Tracer Study Alumni LKP Rumah Gemilang Indonesia (RGI) - Yuanita Sabrina; Muhammad Nurtanto; Vera Utami Gede Putri; Constantinus Rudy Prihantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of job mismatch is one of the challenges in the development of vocational education and training because it indicates a discrepancy between the competencies possessed by graduates and the requirements of the jobs they hold. This situation can affect the effectiveness of training in preparing a workforce that meets the needs of industry, business, and the workforce (IDUKA). This study aims to analyze job mismatch in non-formal vocational training based on the results of a tracer study of alumni from the Rumah Gemilang Indonesia Training and Course Institute (LKP). The study employs a quantitative approach with a descriptive design. Data were collected through a tracer study using an online questionnaire involving 72 alumni of the Rumah Gemilang Indonesia Training Center. Data analysis was conducted using descriptive statistics, including frequency, percentage, and mean. The results indicate that the majority of alumni have entered the workforce, with 38.9% working in fields aligned with their training and 27.8% working in fields not aligned with the training they received. The indicator with the highest average score was “training that helps prepare for employment or entrepreneurship” (4.43), while the lowest-scoring indicator was “discrepancies between training content and the requirements of current jobs” (3.06). The research findings indicate that non-formal vocational training has made a positive contribution to improving graduates’ work readiness; however, there are still signs of a job mismatch, as evidenced by the proportion of graduates working outside their field of training, the need for additional training, and the demand for new competencies after entering the workforce. Therefore, the results of the tracer study should be utilized as a basis for program evaluation through curriculum updates, strengthened collaboration with industry partners, and enhanced practice- and technology-based learning to improve the relevance of graduates’ competencies to labor market needs.